2018
DOI: 10.4103/aer.aer_80_18
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of the efficacy and safety of midazolam, ketamine, and midazolam combined with ketamine administered nasally for premedication in children

Abstract: Background:In this prospective, randomized study, we evaluated the intranasal administration of Midazolam ketamine combination, midazolam, and ketamine in premedication for children.Material and Methods:We studied 60 American Society of Anesthesiology physical status Classes I and II children aged between 1 and 10 years undergoing ear nose throat operations. All cases were premedicated 15 min before operation with intranasal administration of 0.2 mg/kg midazolam in Group M, 5 mg/kg Ketamine in Group K, and 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Excessive salivation associated with ketamine was absent at the dose 2 mg kg -1 intranasally in our study, similarly to the study of Bhat et al [7,15]. The study conducted by Akcay et al [14] showed no emergence delirium or other complications, highlighting the safety of na sal ketamine with midazolam as a premedicant in paediatric patients. However, we did not follow the patients in the postoperative period.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Excessive salivation associated with ketamine was absent at the dose 2 mg kg -1 intranasally in our study, similarly to the study of Bhat et al [7,15]. The study conducted by Akcay et al [14] showed no emergence delirium or other complications, highlighting the safety of na sal ketamine with midazolam as a premedicant in paediatric patients. However, we did not follow the patients in the postoperative period.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, an intranasal dose of 0.12 mg kg -1 midazolam, 1 μg kg -1 dexmedetomidine, and 2 mg kg -1 ketamine in combination for premedication was chosen, similarly to previous studies [7,14]. These doses produced good sedation and parental sepa ration with stable haemodynamics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Midazolam is a common sedative drug delivered to pediatric patients orally to reduce anxiety in the dental clinic [ 6 , 9 , 10 ]. Midazolam is a benzodiazepine derivative that has sedative, anxiolysis, and anterograde amnesia properties with a wide margin of safety [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%